Pengaruh Pemberian Puding Daun Kelor (Moringa oleifera) terhadap Produksi Air Susu Ibu (ASI) pada Ibu Menyusui di Wilayah Kerja Puskesmas Kelurahan Cawang Jakarta Timur - Indri Pratiwi; Mia Srimiati (HB PRESS, 2020)
The increasing presentation of exclusive breastfeeding is still below the national target, one of the obstacles of that issue is the lack of mother breast milk volume. Therefore, need an effort to increase breastmilk production. Moringa leaves contain phytosterol compounds that can facilitate breastmilk production. This study aimed to analyze the effect of Moringa leaf pudding on breastmilk production for breastfeeding mothers at ??Puskesmas Kelurahan Cawang, East Jakarta. This was an experimental study with a pretest-posttest control group design to evaluate the difference of milk production before and after the mother consumed moringa leaf pudding. The baby weight was an indicator of the mother breastmilk production. Therefore, the population on this research were mothers and babies, the mothers are given 250 grams of moringa leaf pudding per day for seven days, then the baby weight was measured before and after treatment. The mother as a subject have to meet the inclusion criteria such as mothers of infants age 0-6 months, exclusive breastfeeding , do not smoke, do not drink alcohol, do not have infectious and degenerative diseases. The analysis showed that there was a significant effect on Moringa leaf pudding on baby weight in the intervention group (p = 0.03), while there was no significant difference in the control group (p = 0.461). The conclusion is Moringa pudding could increase the breastmilk production of mother who consumed it for seven days.